Optimization strategies of ultrasonic-assisted digestion of printed circuit board prior to determination of copper and lead - Abubakar, Kasimu (2020)
Over the past few decades, waste management has become a subject of global interest not only for environmental reasons but also for value-added goods that it provides. The use of hydrometallurgy in electronic waste (e-waste) treatment is effective in metal recovery while at the same time curtailing the waste disposal rate into the ecosystem to some degree. Nevertheless, there is growing concern over the use of concentrated acid due to the correlation of secondary pollution with its disposal. The purpose of the present study is to investigate a suitable method to efficiently recover copper (Cu) and lead (Pb) from waste mobile phone printed circuit boards (PCBs). A hydrometallurgy method was developed for effective metal leaching while maintaining low acid concentrations. Preliminary experiments were conducted to establish a suitable solvent with better dissolution strength for the target metals. Effect of four parameters viz. acid concentration, the molar ratio (HCl: HNO3), time (min) and temperature (°C) were studied using one-variable-at-a-time (OVAT) and multivariate response surface methodology (RSM) optimization. Results obtained showed that 95% Cu and 86% Pb yield were achieved using the RSM method and remarkably, 107% Cu was recovered and a lesser 91% Pb was recorded via the OVAT method. Atomic absorption spectrometer was used in determination of Cu and Pb, relative standard deviation (RSD) for intra-day precision and inter-day were 5.3%, 5.0% and 12.7%, 6.3% respectively. Limit of detection (LOD) and limit of quantitation (LOQ) obtained were 0.082 µg/g and 0.312 µg/g (Pb) whereas 0.02 µg/g and 0.064 µg/g (Cu) were recorded. Overall, the method demonstrates a significant recovery rate, thus, it could be deployed in the dissolution of metals from e-waste. Although OVAT approach gave better recovery rates, RSM seems to be more practical due to the interaction factor.